The Influence Of Risk Management Culture On Project Time Control In Construction Projects: A Random Forest Approach - Kartika Sari, Feby; Nugroho , M. Sapto; Prasetyo, Ryan Faza; Faisal, Ulfa Fatmasari; Wijaya, M. G. Wisnu; Bonastria, Citra Mira Dewi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Managing time is crucial in construction projects, as schedule deviations caused by complexity and external risks often lead to costly delays. This study aims to analyze how risk management culture influences time control in high-rise building construction projects. A mixed-methods approach was employed: first, risk management culture variables were qualitatively identified through in-depth interviews; then, a quantitative analysis was conducted using questionnaires distributed to project managers, construction managers, and financial managers. The data were analyzed with the Random Forest algorithm, chosen for its predictive accuracy. Risk management culture variables (X1–X23) were adapted from ISO 31000:2018, while project time control was measured using the Schedule Performance Index (SPI). The results indicate that a risk management culture has a significant and positive impact on project time control. The most influential factors were the documentation of the risk register (X23), the integration of risk evaluation into decision-making (X16), and continuous monitoring and review (X20). Conversely, formal aspects, such as risk management policies (X2) and training programs (X11), showed a relatively lower influence. These findings suggest that active implementation of risk management culture in daily operations contributes more directly to improving schedule performance. The study highlights the importance of accurate risk documentation, risk-informed decision-making, and adaptive monitoring as priorities for achieving effective time control in construction projects.